Sliding-mode approaches to control a microinverter based on a quadratic boost converter - Valderrama-Blavi, Hugo (2020)
A comparative analysis of the dynamic features of a step-up microinverter based on the cascade connection of two synchronized boost stages and a full-bridge is presented in this work. In the conventional approach the output of the cascaded boost converter is a 350–400 DC voltage that supplies the full-bridge that makes the DC-AC conversion. Differently from the classical approach, in this work, the cascaded boost converter delivers a sinusoidal rectified voltage of 230 Vrms to the full-bridge converter that operates as unfolding stage. This stage changes the voltage sign of one of every two periods of the rectified sinusoidal signal providing the final output AC waveform. In contrast to a classical full-bridge inverter, the unfolding stage lacks output filter, and has zero order dynamics. Thus, the approach presented here implies a second order dynamics reduction that will be increased applying sliding motions to control the system. After introducing the inverter circuit, two sliding control alternatives, input current mode and pseudo-oscillating mode, are presented. Both alternatives are analyzed, simulated, and verified experimentally. Furthermore, detailed description of the microinverter power stage and control circuits are also given.